Penerapan Intervensi Edukasi terhadap Self-Management, Self Efficacy dan Nilai Gula Darah pada Pasien Diabetes Melitus - Silalahi, Lenny Erida; Irawati, Diana; Anggraeni, Dewi; Jumaiyah, Wati; Abriyanti, Rika Mustika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to implement Evidence-Based Nursing Practice (EBNP) with educational interventions on self-management, self-efficacy, and blood sugar values in DM patients at Tarakan Hospital, Jakarta. This research method uses quasi-experimental. The research results show that the p-value of self-management with self-efficacy is (r=0.464, p=0.001). The conclusion is that fasting blood sugar changes will impact postprandial blood sugar changes, and self-management will influence changes in respondents' self-efficacy. Keywords: DM, Self-management, Self-efficacy